Pengaruh Fraud Risk Assessment Terhadap Kualitas Audit Badan Keuangan dan Aset Daerah Kota Bitung - Mecky Wurangian; Nur Qhomaria Anjani Paputungan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Fraud in the accounting field is fraud that involves data manipulation, asset theft, or other violations of business ethics. The Bitung City Regional Financial and Asset Agency is one of the agencies that is vulnerable to fraud. BKAD has the task of assisting the Mayor through the Regional Secretary in carrying out supporting functions in government affairs in the field of finance and regional assets. The research method used in this research is the quantitative method, a quantitative method, namely a research method that uses numbers and statistics in collecting and analyzing data that can be measured. The results of this research indicate that Fraud Risk Assessment has a significant positive effect on Time Pressure on Regional Financial Agencies and Assets. Auditors do not ignore audit procedures and can complete the audit process well even though the time pressure available to complete the audit is limited, auditors are able to indicate the occurrence of fraud either from suspicious documentation or changes in someone's behavior. Researchers concluded that Fraud Risk Assessment had a significant positive effect on Internal Control at the Regional Financial and Asset Agency (BKAD). This indicates that the higher the level of fraud risk assessment possessed by the auditor, the greater the auditor's ability to detect fraud.